PERAN GURU PROFESIONAL UNTUK MENCIPTAKAN KELAS YANG AKTIF DAN BERMAKNA - Hanifah Sabrina Aulia; Nabila Fitriananda; Munawir (STKIP Subang, 2026)
The role of professional teachers becomes a key element in creating active and meaningful learning environments amid the dynamic demands of 21st-century education. The shift from teacher-centered to student-centered learning requires teachers not only to deliver content but also to facilitate engaging and participatory learning experiences. This study aims to analyze how professional teachers contribute to fostering student engagement and constructing meaningful learning processes. A qualitative approach with a library research design was employed, utilizing relevant and credible sources such as academic journals, books, and official documents. Data were collected through documentation techniques and analyzed using content analysis, including data reduction, data display, and integrative conclusion drawing. The findings indicate that professional teachers perform multiple roles, including as educators, facilitators, motivators, and learning managers, which directly influence students’ level of participation and depth of understanding. Learning environments that are designed to be active and contextual are shown to enhance critical thinking skills, social interaction, and the ability to connect knowledge with real-life situations. Thus, the effectiveness of learning is not solely determined by the methods applied, but also by the teacher’s ability to integrate professional competencies into classroom practices in a comprehensive and meaningful way.